A novel colony‐stimulating factor 1 (CSF1) translocation involving human endogenous retroviral element in a tenosynovial giant cell tumor. Issue 4 (5th January 2023) - Lipplaa, Astrid; Meijer, Debora; van de Sande, Michiel A. J.; Gelderblom, Hans; Bovée, Judith V. M. G.; Mei, Hailiang; Szuhai, Karoly
Abstract: Tenosynovial giant cell tumors (TSGCTs) are rare tumors arising in tendons or the synoviae of joints and bursae. The localized type is benign while the diffuse type shows expansive growth leading to greater morbidity and is therefore considered locally aggressive. Typical recurrent chromosomal aberrations are found in the majority of TSCGT and the CSF1 gene is frequently involved. In this article, we describe a newly identified gene fusion mediated by an inversion in a case of diffuse TSGCT. Multicolor‐fluorescence in situ hybridization (FISH) molecular karyotyping identified a pericentric inversion of chromosome 1 in 7 out of 17 analyzed cells 46, XX, inv(1)(p13.3q24.3) [7]/46, XX [10], and with interphase FISH the involvement the CSF1 locus was detected. After performing transcriptome sequencing analysis for fusion detection, only one out of five fusion gene algorithms detected a fusion involving the CSF1 gene product. The resulting chimera fuses a sequence from a human endogenous retrovirus (HERV) gene to CSF1 Exon 6 on chromosome 1, abrogating the regulatory element of the 3′ untranslated region of the CSF1 gene. This new translocation involving Exon 6 of the CSF1 gene fused to 1q24.1, supports the hypothesis that a mutated CSF1 protein is likely to play a vital role in the pathogenesis of TSGCT. The role of the HERV partner identified as a translocation partner, however, remains unclear. Our data add to the complexity of involved translocation partners in TSGCT and point to the potential difficulty of identifying fusion partners in tumor diagnostics using transcriptome sequencing when HERV or other repeat elements are involved.